Diversified Cultural Representations on Malaysian Television - Salleh, Sabariah Mohamed (Richtmann Publishing, 2012)
The Malaysian society is known for its rich traditional beliefs and culture and is home to people of various ethnicities, whichinclude Malays, Chinese, Indians and various aboriginal tribes. Admittedly, there are social distances between the various races andâ€œmost Malays do not know Chinese values very well and most Chinese are quite ignorant of Malay values, despite the fact that they havebeen living side by side for so longâ€ (Syed Hussin, 2008: 171). This is where mass media, according to Siapera (2010), especiallytelevision, can play a big role. In light of this matter, Syed Hussin (2008) commented that mass communication has not been used to itsfull effect to promote a better understanding of people of different cultures and values. Hence, the core of this paper involves looking atthe content of television programs in Malaysia, in order to unearth how the diversified cultures are being portrayed on television. Byrelating it to the regimes of representation (Siapera, 2010) I intend to investigate if the various races are equally represented. Also, I aminterested to gauge the possible aspects one can learn about their culture from the program. To help answer this question, a qualitativecontent analysis was conducted on Buletin Utama1, to ascertain the forms of culture that are being represented in the program mostwatched by the Malaysian audience.